2020
DOI: 10.1089/gtmb.2019.0164
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA SERTAD2-3 Inhibits Osteosarcoma Proliferation and Migration by Competitively Binding miR-29c

Abstract: Background: Osteosarcoma (OS) is a malignant tumor disease with high morbidity and mortality in children and adolescents. Recently, attention has been focused on the effects of long noncoding RNAs (lncRNAs) on tumor biology. In this study, we identified the role of lnc-SERTAD2-3 in the development of OS. Materials and Methods: Sixty OS samples and adjacent tissues were collected to determine the relationship between lnc-SERTAD2-3 levels and clinicopathological characteristics. Quantitative real-time PCR (qPCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Moreover, our studies have reported that the apoptosis-related miRNAs miR-130a, miR-222, miR-195, miR-29c, miR-92a-1, and miR-216a were aberrantly expressed in baicalin-induced apoptosis in MG63 cells. Interestingly, among them, miR-195, miR-29c, and miR-92a-1 were reported in a previous study of osteosarcoma [72][73][74], indicating the high degree of confidence in our sequencing results. This is the first study to show the aberrant expression of ENST00000449500 and ENST00000607286 in MG63 cells and indicates a potential prognostic role of this 2-lncRNA signature in MG63 cells.…”
supporting
confidence: 64%
“…Moreover, our studies have reported that the apoptosis-related miRNAs miR-130a, miR-222, miR-195, miR-29c, miR-92a-1, and miR-216a were aberrantly expressed in baicalin-induced apoptosis in MG63 cells. Interestingly, among them, miR-195, miR-29c, and miR-92a-1 were reported in a previous study of osteosarcoma [72][73][74], indicating the high degree of confidence in our sequencing results. This is the first study to show the aberrant expression of ENST00000449500 and ENST00000607286 in MG63 cells and indicates a potential prognostic role of this 2-lncRNA signature in MG63 cells.…”
supporting
confidence: 64%
“…28 In recent years, a large number of lncRNAs are discovered as new regulatory molecules in cancer biology. 29,30 For example, lncRNA UCA1 is upregulated in gliomas and promotes cancer cell proliferation. 31 LncRNA ANRIL is overexpressed during glioma development and is associated with unfavorable pathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma (OS) is identified as a common malignancy amongst children and teenagers [ 1 ]. Despite the great progress in the therapeutics of OS, the prognosis remains unsatisfactory due to distant metastasis and recurrence [ 2 ].…”
Section: Introductionmentioning
confidence: 99%